Indicators of conservation value of Azorean caves based on its arthropod fauna - Borges, Paulo A. V. (2008)
All Azorean lava-tubes and volcanic pits with fauna were evaluated for species diversity and rarity based on arthropods. To produce an unbiased multiple-criteria index (importance value for conservation, IV-C) incorporating arthropod species diversity based indices and indices qualifying geological and management features (e.g. diversity of geological structures, threats, accessibility, etc.), an iterative partial multiple regression analysis was performed. In addition, the complementarity method (using heuristic methods) was used for priority-cave analyses. Most hypogean endemic species have restricted distributions, occurring only in one cave. It was concluded that several well-managed protected caves per island are absolutely necessary to have a good fraction of the endemic arthropods preserved. For presence/absence data, suboptimal solutions indicate that at least 50% lava-tubes with known hypogean fauna are needed if we want that 100% of endemic arthropod species are represented in a minimum set of reserves. Based both on the uniqueness of species composition and/or high species richness and geological value of the caves, conservation efforts should be focused on the following caves: Gruta da Beira, Algar das Bocas do Fogo (S. Jorge); Montanheiros, Henrique Maciel, Soldão, Furna das Cabras II and Ribeira do Fundo (Pico); Algar do Carvão, Balcões, Agulhas and Chocolate (Terceira); Água de Pau (S. Miguel); Anelares and Parque do Capelo (Faial).